2019
DOI: 10.1371/journal.pone.0225247
|View full text |Cite
|
Sign up to set email alerts
|

The association between chronic periodontitis and oral Helicobacter pylori: A meta-analysis

Abstract: BackgroundEpidemiological studies have shown that gastrointestinal Helicobacter pylori (H. pylori) infection is the main cause of chronic gastritis, but the relation between oral H. pylori and chronic periodontitis (CP) remains uncertain. A meta-analysis of published papers was performed to elucidate the correlation between oral H. pylori and CP.MethodTo perform this meta-analysis, we searched papers published from 2000 to 2018 on PubMed, OVID, Springer Link, Chinese National Knowledge Infrastructure (CNKI) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
0
20
0
5
Order By: Relevance
“…In the oral cavity, the microorganisms in dental biofilm and saliva may play a role as a potential reservoir for H. pylori [ 41 ]. Recently, oral H. pylori was found to a potential risk factor for the development of CP [ 42 ]. In addition, a systematic review demonstrated a great reduction in H. pylori among patients who received periodontal therapy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the oral cavity, the microorganisms in dental biofilm and saliva may play a role as a potential reservoir for H. pylori [ 41 ]. Recently, oral H. pylori was found to a potential risk factor for the development of CP [ 42 ]. In addition, a systematic review demonstrated a great reduction in H. pylori among patients who received periodontal therapy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis was performed on 11 studies including 1993 participants (1319 with chronic periodontitis (CP) and 674 controls) who had oral and gastric H pylori tested by PCR and rapid urease test. When compared to the H pylori ‐negative population, H pylori ‐positive patients had a significantly increased risk of CP (OR = 3.42, 95% CI = 2.71‐4.31) 19 . Another meta‐analysis of 13 studies involving 6800 patients, also suggested that the risk of periodontal diseases in the patients with oral H pylori positivity was 2.31 (95% CI, 1.00‐2.68) times higher than those with H pylori negativity 20 .…”
Section: Helicobacter Pylori Acquisitionmentioning
confidence: 99%
“…Generally, all ages are affected, this in combination with the condition of infection at the right time by the specific bacterium with good oral hygiene; conditions that must simultaneously be in combination with each other. The study aims to collect retrospective and cross-sectional data on the prevalence of chronic periodontitis [5][6][7][8][9][10]. Having both types of studies for the purpose of data collection, it is possible to find possible correlations on the effect of risk factors for the occurrence of chronic periodontitis, the effect of local dental factors on the formation of bacterial plaque and then on the occurrence of chronic, local or generalized periodontitis, or the extent of this infection divided or not depending on the sex, age of the affected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Having both types of studies for the purpose of data collection, it is possible to find possible correlations on the effect of risk factors for the occurrence of chronic periodontitis, the effect of local dental factors on the formation of bacterial plaque and then on the occurrence of chronic, local or generalized periodontitis, or the extent of this infection divided or not depending on the sex, age of the affected individuals. An important element that gives the opportunity through this study to collect and process the recorded data, is the possibility of finding correlations of this diagnosis and the presence of other lesions of hard and soft tissues [2,5,7,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%